A comparative analysis of polyfunctional T cells and secreted cytokines induced by Bacille Calmette-Guérin immunisation in children and adults. - Nicole Ritz; Madeleine Strach; Carmen Yau; Binita Dutta; Marc Tebruegge; Tom G Connell; Willem A Hanekom; Warwick J Britton; Roy Robins-Browne; Nigel Curtis (PLoS ONE, 2012)
BCG vaccine is one of the most commonly-administered vaccines worldwide. Studies suggest the protective efficacy of BCG against TB is better for children than for adults. One potential explanation is that BCG induces a better protective immune response in children. Twenty six children and adults were immunised with BCG. The proportion of Th1-cytokine-producing mycobacterial-specific T cells, and the concentrations of secreted cytokines, were measured before and 10 weeks after BCG immunisation. A significant increase in the proportion of mycobacterial-specific cytokine-producing T cells was observed in both age groups. After BCG immunisation, children and adults had comparable proportions of mycobacterial-specific polyfunctional CD4 T cells when measured relative to the total number of CD4 T cells. However, relative to the subset of Th-1-cytokine-producing CD4 T cells, the proportion of polyfunctional cells was greater in children. Concentrations of secreted cytokines were comparable in children and adults. These findings suggest that the mycobacterial-specific cell-mediated immune response induced by BCG immunisation in children and adults is similar. The implication of a shift to a more polyfunctional immune response within the Th1-cytokine-producing CD4 T cells in children is uncertain as this aspect of the immune response has not been assessed as a potential correlate of protection against TB.